Linguatulosis in small ruminants in southeastern Iran: Epidemiological, histopathological and phylogenetic findings and its public health importance. (March 2021) - Bamorovat, Mehdi; Sharifi, Iraj; Oliaee, Razieh Tavakoli; Aflatoonian, Mohamad Reza; Nejad Almani, Pooya Ghasemi; Derakhshani, Ali; Nasibi, Saeed; Khedri, Javad; Khirandish, Reza; Mohammadi, Mohammad Ali
Abstract: Linguatulosis, as a zoonotic disease, can infect most ruminants and cause accidental infections in humans. The objective of this study was to explore the epidemiological, histopathological and phylogenetic profiles of Linguatula serrata infection in sheep and goats and its public health importance during 2015–2018. Mesenteric lymph nodes (MLNs) and liver tissue of goats and sheep were selected randomly in Kerman slaughterhouse. Nymphal samples were used for DNA extraction, amplification and subsequently phylogenetic analysis using 18s rRNA and cytochrome C oxidase subunit 1 (cox1). Overall, of 828 examined livestock, 179 (42.4%) goats and 71 (17.5%) sheep were found to be infected with the nymphal stage of L. serrata . A significant difference was observed between linguatulosis and age. In the histopathological assessment, longitudinal and transverse sections of L. serrata nymphs were observed within the cyst-like spaces surrounded by a wall of fine fibrosis and compact lymphocytes. Moreover, comparing with the L. serrata reference sequences, we found only a single nucleotide change in our goat haplotype in 18s genetic region; while much nucleotide variations were observed in cox1 gene sequences. The results of the present study showed a high infection rate among goats and sheep in southeastern Iran. A better understanding of the disease could be achieved when the parasite species, their molecular characterization and the extent of infection in the area are determined. It is fundamental to select a comprehensive control program in order to take proper preventive and therapeutic measures against the infection. Highlights: High infection rate of linguatulosis was identified in mesenteric lymph nodes (MLNs) of goats and sheep. A significant difference was observed between linguatulosis and age in both groups. Longitudinal and transverse sections of Linguatula serrata nymphs were observed within the cyst-like spaces in MLNs. Phylogenetic analysis represented more nucleotide variations in the sequences of cox1 gene region than 18s gene region.